Internet of things and Big Data as potential solutions to the problems in waste electrical and electronic equipment management: An exploratory study. (October 2017) - Gu, Fu; Ma, Buqing; Guo, Jianfeng; Summers, Peter A.; Hall, Philip
Highlights: Major problems in current WEEE management have been identified. Communication technologies enabling smart WEEE management are described. Framework of implementing the IoT and the Big Data technologies is proposed. Application scenarios based on real-world cases are constructed and discussed. Challenges as well as future research opportunities are identified. Abstract: Management of Waste Electrical and Electronic Equipment (WEEE) is a vital part in solid waste management, there are still some difficult issues require attentionss. This paper investigates the potential of applying Internet of Things (IoT) and Big Data as the solutions to the WEEE management problems. The massive data generated during the production, consumption and disposal of Electrical and Electronic Equipment (EEE) fits the characteristics of Big Data. Through using the state-of-the-art communication technologies, the IoT derives the WEEE "Big Data" from the life cycle of EEE, and the Big Data technologies process the WEEE "Big Data" for supporting decision making in WEEE management. The framework of implementing the IoT and the Big Data technologies is proposed, with its multiple layers are illustrated. Case studies with the potential application scenarios of the framework are presented and discussed. As an unprecedented exploration, the combined application of the IoT and the Big Data technologies in WEEE management brings a series of opportunities as well as new challenges. This study provides insights and visions for stakeholders in solving the WEEE management problems under the context of IoT and Big Data.